A short overview of the physicochemical properties of cold-bonded alkali-activated lightweight aggregates and preliminary examinations of their usability for plant growth - Frohmüller, Max O.; Wichmann, Isabelle; Stephan, Dietmar (Frontiers in Environmental Engineering, 2025)
IntroductionA novel way to upcycle fine concrete or brick demolition waste (<2 mm) to akaliactivated lightweight aggregates (ALA) was described recently. As pollutant burdens in these precursors are closely controlled by federal law in Germany, the aggregates produced in this study could be used in direct contact with the environment.MethodsTherefore, different parameters of ALA, lightweight expanded clay aggregates (LECA), and plant granulate were measured and compared, such as pH buffering, heavy metal leaching, pH, and conductivity in solution, pore size distribution, available water content (AWC), and dissolvable macronutrients. Additional plant growth experiments assessed the aggregate’s feasibility as a substrate compared to or as an improvement for lightly acidic soil, with different mixing ratios between LUFA reference soil and ALA.ResultsThese investigations showed high phytotoxicity, which might be explained by salinization (∼3.6 or 4.6 times higher conductivities than plant granulate) and by ALA’s elevated pH (>12). The latter may be used for soil improvements like liming, but a neutralization capacity of only ∼1.7% compared to pure CaO was reached. Similar to this, ALA’s AWC stayed below 1/6 of LECA’s AWC. Both brick or concrete powder aggregates (BPA or CPA) provided comparable or higher amounts of Ca, K, and P relative to plant granulate and exhibited heavy metal loads below the German federal limit values.DiscussionWhile these findings hinted that ALA could act as soil improvements in the future, this use case is not feasible without significant improvements to either ALA’s production process or post-treatment.